1999
DOI: 10.1093/qjmed/92.9.519
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypertension in patients developing end-stage renal failure

Abstract: The benefits of treating hypertension include preventing or delaying the progression of chronic renal failure, and reducing the cardiovascular complications of patients with renal disease. We examined how well hypertension had been managed in all 145 patients from a single health district who started dialysis during a 3-year period. Data relating to management of hypertension, including all blood pressure readings, were obtained from their general practice and hospital case notes. The anonymized data were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…It is of utmost importance that the blood pressure of CKD patients is strictly controlled, as this will minimize the disease's progression and reduce the risk of cardiovascular disease. 34 Supporting this statement is the Multiple Risk Factor Intervention Trial, which found that higher blood pressure was an independent risk factor of progression to ESRD. 35 The World Health Organization 36 and KDOQI 37 generally recommend that blood pressure values of ≤ 130/85 mmHg (≤ 140/90 mmHg in patients over 60 years of age) are optimal for patients with CKD.…”
Section: Early Referral For Nephrological Treatmentmentioning
confidence: 97%
“…It is of utmost importance that the blood pressure of CKD patients is strictly controlled, as this will minimize the disease's progression and reduce the risk of cardiovascular disease. 34 Supporting this statement is the Multiple Risk Factor Intervention Trial, which found that higher blood pressure was an independent risk factor of progression to ESRD. 35 The World Health Organization 36 and KDOQI 37 generally recommend that blood pressure values of ≤ 130/85 mmHg (≤ 140/90 mmHg in patients over 60 years of age) are optimal for patients with CKD.…”
Section: Early Referral For Nephrological Treatmentmentioning
confidence: 97%
“…Second, the burden and importance of RH in CKD is currently unknown. Indeed, several surveys in CKD patients demonstrate a high incidence of uncontrolled hypertension in clinical practice [14][15][16][17][18][19][20][21] ; however, the value of these surveys is limited due to the absence of information on the number/dose of antihypertensive agents utilized and the cross-sectional design of these audits which precludes any evaluation of the effects of intensification of antihypertensive therapy on BP control. Landmark hypertension trials in CKD also attest to the difficulty of achieving BP goal in as many as 50% of non-diabetic and 70% of diabetic patients despite titration of antihypertensive therapy to goal and the use of 3.5-4.5 antihypertensive agents per patient [7,[22][23][24] .…”
Section: Burden Of Resistant Hypertension Inmentioning
confidence: 99%
“…In a study of 140 British dialysis subjects, Dasgupta et al found that only 45% achieved diastolic BP Ͻ90 mm Hg before the onset of end-stage renal disease. 23 Schwenger and Ritz 24 observed that among 201 German patients with serum creatinine Ն1.4 mg/dL managed in a nephrology clinic, the mean BP achieved BP was 140/85.…”
Section: Discusssionmentioning
confidence: 99%